Seasonal to Decadal Predictions With MIROC6: Description and Basic Evaluation. (2nd December 2020) - Kataoka, Takahito; Tatebe, Hiroaki; Koyama, Hiroshi; Mochizuki, Takashi; Ogochi, Koji; Naoe, Hiroaki; Imada, Yukiko; Shiogama, Hideo; Kimoto, Masahide; Watanabe, Masahiro
Abstract: The present paper presents results of seasonal‐to‐decadal climate predictions based on a coupled climate model called the Model for Interdisciplinary Research on Climate version 6 (MIROC6) contributing to the Coupled Model Intercomparison Project Phase 6 (CMIP6). MIROC6 is initialized every year for 1960–2018 by assimilating observed ocean temperature and salinity anomalies and full fields of sea ice concentration and by prescribing atmospheric initial states from reanalysis data. The impacts of updating the system on prediction skill are then evaluated by comparing hindcast experiments between the MIROC6 prediction system and a previous system based on MIROC version 5 (MIROC5). Skill of seasonal prediction is overall improved in association with representation and initialization of El Niño/Southern Oscillation (ENSO), the Quasi‐Biennial Oscillation (QBO), and the Northern Hemisphere sea ice concentration in MIROC6. In particular, the QBO is skillfully predicted up to 3 years ahead with a maximum anomaly correlation exceeding r  = 0.8. The prediction skill for the North Atlantic Oscillation in winter is also enhanced, but the prediction still suffers from model's inherent errors. On decadal timescales, MIROC6 has a larger fraction of areas of the globe with better surface temperature skill at all lead times than MIROC5, and it has predictive skill in the annual‐mean sea surface temperature (SST) in the North Atlantic and the Pacific. In particular, MIROC6 hindcasts at 2–5 years lead time are able to capture the spatial structure of SST changes in the North Pacific and the eastern tropical Pacific associated with the 1970s regime shift better than MIROC5 hindcasts. Plain Language Summary: The present paper presents results of seasonal‐to‐decadal climate predictions based on a coupled climate model called the Model for Interdisciplinary Research on Climate version 6 (MIROC6) contributing to the Coupled Model Intercomparison Project Phase 6 (CMIP6). The MIROC6 prediction system takes into account observed ocean, sea ice, and atmospheric conditions in the initialization, whereas its predecessor (MIROC5) considers observed ocean conditions only. Experiments with MIROC6 without initialization are also carried out in order to quantify impacts of initialization. Prediction skill of MIROC6 new prediction system several months to a year ahead is improved over MIROC5. In particular, the tropical variability in the stratosphere, which could be a key for predictions of the North American and European winter climate, is well predicted beyond a year. Also, while the overall improvement over MIROC5 is modest, MIROC6 has substantial skill for predictions of annual‐mean sea surface temperatures, particularly over the North Atlantic and the Pacific several years in advance. MIROC6 is able to better predict the variability in the North Pacific and the eastern tropical Pacific than initialized MIROC5 and uninitialized MIROC6 experiments, highlighting the importance of the system updates and observed information. Key Points: A seasonal to decadal prediction system with MIROC6 was developed for contributing to the Coupled Model Intercomparison Project Phase 6 Seasonal predictions of El Niño, North Atlantic Oscillation, Quasi‐Biannual Oscillation, and sea ice are improved over its predecessor The new system better captures the spatial structure of the 1970s Pacific regime shift in sea surface temperatures